Single and double stereoselective fluorination of (E)-allylsilanes - Sawicki, Marcin; Kwok, Angela; Tredwell, Matthew; Gouverneur, Véronique (Beilstein Journal of Organic Chemistry, 2007)
Acyclic allylic monofluorides were prepared by electrophilic fluorination of branched (E)-allylsilanes with Selectfluor. These reactions proceeded with efficient transfer of chirality from the silylated to the fluorinated stereocentre. Upon double fluorination, an unsymmetrical ethyl syn-2,5-difluoroalk-3-enoic ester was prepared, the silyl group acting as an anti stereodirecting group for the two C-F bond forming events.

Modern Fluoroorganic Chemistry - Kirsch, P. (Weinheim, 2004)

(untitled) - Hiyama, T.; Shimizu, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Bobbio, C.; Gouverneur, V. (Org. Biomol. Chem., 2006)

(untitled) - Davies, A. F.; Han, W. (Tetrahedron Lett., 1992)

(untitled) - Davies, A. F.; Qi, H. (Tetrahedron Lett., 1996)

(untitled) - McAtee, J. J.; Schinazi, R. F.; Liotta, D. C. (J. Org. Chem., 1998)

(untitled) - Enders, D.; Potthof, M.; Rabee, G.; Runsink, J. (Angew. Chem., Int. Ed., 1997)

(untitled) - Enders, D.; Faure, S.; Potthoff, M.; Runsink, J. (Synthesis, 2001)

(untitled) - Konas, D. W.; Coward, J. K. (J. Org. Chem., 2001)

(untitled) - Andrews, P. C.; Bhaskar, V.; Bromfield, K. M.; Dodd, A. M.; Duggan, P. J.; Duggan, S. A. M.; McCarthy, T. M. (Synlett, 2004)

(untitled) - Mohar, B.; Sterk, D.; Ferron, L.; Cahard, D. (Tetrahedron Lett., 2005)

(untitled) - Giuffredi, G.; Odell, B.; Bobbio, C.; Gouverneur, V. (J. Org. Chem., 2006)

(untitled) - Purser, S.; Odell, B.; Claridge, T. D. W.; Moore, P. R.; Gouverneur, V. (Chem.–Eur. J., 2006)

(untitled) - Lam, Yh; Bobbio, C.; Cooper, I. R.; Gouverneur, V. (Angew. Chem., Int. Ed., 2007)

(untitled) - Purser, S.; Wilson, C.; Gouverneur, V. (Synlett, 2007)

(untitled) - Tredwell, M.; Tenza, K.; Pacheco, M.; Gouverneur, V. (Org. Lett., 2005)

(untitled) - Teare, H.; Huguet, F.; Tredwell, M.; Thibaudeau, S.; Luthra, S. K.; Gouverneur, V. (ARKIVOC, 2007)

(untitled) - Fleming, I.; Dunogues, J.; Smithers, R. (Org. React., 1989)

(untitled) - Masse, C. E.; Panek, J. S. (Chem. Rev., 1995)

(untitled) - Fleming, I.; Barbero, A.; Walter, D. (Chem. Rev., 1997)

(untitled) - Chabaud, L.; James, P.; Landais, Y. (Eur. J. Org. Chem., 2004)

(untitled) - Huang, H.; Panek, J. S. (J. Am. Chem. Soc., 2000)

(untitled) - Panek, J. S.; Liu, P. (J. Am. Chem. Soc., 2000)

(untitled) - Liu, P.; Binnun, E. D.; Schaus, J. V.; Valentino, N. M.; Panek, J. S. (J. Org. Chem., 2002)

(untitled) - Lowe, J. T.; Panek, J. S. (Org. Lett., 2005)

(untitled) - Lowe, J. T.; Panek, J. S. (Org. Lett., 2005)

(untitled) - Heitzman, C.; Lambert, W. T.; Mertz, E.; Shotwell, J. B.; Tinsley, J. M.; Va, P.; Roush, W. R. (Org. Lett., 2005)

(untitled) - Beresis, R. T.; Masse, C. E.; Panek, J. S. (J. Org. Chem., 1995)

(untitled) - Masse, C. E.; Knight, B. S.; Stavropoulos, P.; Panek, J. S. (J. Am. Chem. Soc., 1997)

(untitled) - Sparks, M. A.; Panek, J. S. (J. Org. Chem., 1991)

(untitled) - Hunter, L.; O'Hagan, D.; Slavin, A. M. Z. (J. Am. Chem. Soc., 2006)

(untitled) - Thibaudeau, S.; Fuller, R.; Gouverneur, V. (Org. Biomol. Chem., 2004)

(untitled) - Kitano, Y.; Matsumoto, T.; Sato, F. (Tetrahedron, 1988)

(untitled) - Resnati, G.; DesMarteau, D. D. (J. Org. Chem., 1991)

(untitled) - Poli, G. (Tetrahedron Lett., 1989)